The Ceramic Traditions in Balochistan - Baloch, Azmat Habeeb (Hanken, 2013)
Balochistan has a very rich cultural heritage. However, the cultural Activities started in Balochistan in Paleolithic times around 35000 B.P as the Paleolithic evidences have been in eastern Balochistan, southeastern Balochistan and Suleman ranges. Mesolithic evidences have been found in Zhob are, while the Neolithic cultural activities are not limited to only one region of Balochistan, they are found in all parts of Balochistan. In this regard, Mehrgarh – the first Neolithic settlement not only in Balochistan, in fact, in the South Asia marked the beginning of so many developments that some scholars termed it as “Neolithic Revolution”. The cultural activities don’t end here, they continued later in Chalcolithic Age, Bronze Age, and Iron Age until late historic times. Tradition of Pottery making began at Mehrgarh in the Neolithic period of Balochistan along with many other developments. First potteries were basket marked, then handmade and later with a little development; potteries were made by wheels so the third method is called wheel made potteries. This cultural activity started by people of Mehrgarh, imitated and continued by their successors or contemporary people for a long period with a little change in making technique or decoration. That’s why we have many specimens of various ceramic industries in Balochistan mainly characterized by the style of decoration or making technique. This paper will illustrate these various ceramic industries or traditions as the ceramics are very sensitive and reliable sources which indicate the cultural dynamics in a region.